Gradualny sposób badania mowy pacjentów dorosłych z afazją - Siudak , Anna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
This article is a voice in a streamlined discussion on methods for diagnosing adult patients with aphasia. The variety of aphasic symptoms and the complexity of the clinical picture of patients after neurological incidents often make it impossible to conduct an examination with standardised, well-known methods [see Siudak 2017]. The signals of reluctance towards the methods of examination sent by patients are uttered expressis verbis by people who have overcome aphasia: we need a conversation, not an examination. How then, do we turn diagnosis into a meeting? How can we determine the level of linguistic functioning without having to make the patient aware of what they can no longer do? The Gradual Test Method developed by the author is a research proposal, in which the determination of a patient’s level of language difficulty is based on a gradual transition from easier to more complex structures, without repeating the same procedures many times.